Visualizing Presynaptic Active Zones and Synaptic Vesicles - Heckmann, Manfred; Pauli, Martin (Frontiers in Synaptic Neuroscience, 2022)
The presynaptic active zone (AZ) of chemical synapses is a highly dynamic compartment where synaptic vesicle fusion and neurotransmitter release take place. During evolution the AZ was optimized for speed, accuracy, and reliability of chemical synaptic transmission in combination with miniaturization and plasticity. Single-molecule localization microscopy (SMLM) offers nanometer spatial resolution as well as information about copy number, localization, and orientation of proteins of interest in AZs. This type of imaging allows quantifications of activity dependent AZ reorganizations, e.g., in the context of presynaptic homeostatic potentiation. In combination with high-pressure freezing and optogenetic or electrical stimulation AZs can be imaged with millisecond temporal resolution during synaptic activity. Therefore SMLM allows the determination of key parameters in the complex spatial environment of AZs, necessary for next generation simulations of chemical synapses with realistic protein arrangements.